PEMBELAJARAN DENGAN MODEL KUANTUM DALAM MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS XII IPS 3 SMA NEGERI 8 KOTA BENGKULU TAHUN PELAJARAN 2016/2017 - Andra, Vebbi (Scientia: Jurnal Hasil Penelitian, 2016)
implementation of learning with quantum models in improving learning outcomes in the subjects of Indonesian language class XII IPS 3 SMA (Senior High School) Negeri 8 Bengkulu City academic year 2016/2017, especially regarding the basic competence of writing poetry is to be said to have succeeded. This is evident from the results of tests (evaluation) conducted by teachers to students, where from the stages of learning is done (starting from prasiklus up to cycles I and II) always experience good value improvement continuously.